2021
DOI: 10.1111/jonm.13499
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing career success of clinical nurses in northwestern China based on Kaleidoscope Career Model: Structural equation model

Abstract: Aim: To explore the relationships among self-efficacy, information literacy, social support and career success of clinical nurses and identify factors influencing clinical nurses' career success in northwestern China. Background: Understanding the influencing factors of career success is important for the professional development of nurses and the improvement of clinical nursing quality. Many influencing factors of career success have been identified, but there is no large-scale research on the relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 61 publications
5
40
0
4
Order By: Relevance
“…Moreover, with the improvement of titles, the salary and competitiveness of nurses within the organization will be further improved, which is more conducive to their career development and therefore they have higher career success scores. In the score of career success of administrative position, it can be found that nurses with administrative positions have better scores than general nurses ( Wu et al, 2022 ). This may be due to the fact that head nurses, as management staff, have a certain level of status in the hospital and have the opportunity to participate in hospital policy-making, and that nurses with administrative positions have relatively more time and opportunities to study and pursue further training, so as to improve their career success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, with the improvement of titles, the salary and competitiveness of nurses within the organization will be further improved, which is more conducive to their career development and therefore they have higher career success scores. In the score of career success of administrative position, it can be found that nurses with administrative positions have better scores than general nurses ( Wu et al, 2022 ). This may be due to the fact that head nurses, as management staff, have a certain level of status in the hospital and have the opportunity to participate in hospital policy-making, and that nurses with administrative positions have relatively more time and opportunities to study and pursue further training, so as to improve their career success.…”
Section: Discussionmentioning
confidence: 99%
“…It includes both subjective and objective success, and is an important indicator and variable to evaluate individual career development ( Seibert et al, 1999 ; Eby et al, 2003 ). Currently, studies on career success are mostly focused on the field of management, but in recent years, the number of studies on career fulfillment in the field of nursing field has gradually increased ( Wu et al, 2022 ). Previous studies have shown that career success has a significant positive predictive effect on nurses’ career identity and individual values, which is conducive to motivating nurses’ enthusiasm for work, improve the quality of nursing service, reduce the turnover rate of nurses and stabilize the nursing team ( Dan et al, 2018 ; Zamanzadeh et al, 2019 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one of the few studies adopted a variable‐centred approach focusing on the relationships between individual variables (e.g. career success and related factors; Wu et al, 2022). This approach is limited to reflecting various aspects of career success and restricts appropriate interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Data on other sociodemographic factors (i.e. age, sex and education) were also collected on the basis of previous studies (Wang et al, 2019; Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%